Epea and Grammata : oral and written communication in ancient Greece - Worthington, Ian.; Foley, John Miles. (Mnemosyne, Supplements, 2002)
This volume deals with aspects of orality and oral traditions in ancient Greece, and is a selection of refereed papers from the fourth biennial Orality and Literacy in Ancient Greece conference, held at the University of Missouri Columbia in 2000. The book is divided into three parts: literature, rhetoric and society, and philosophy. The papers focus on genres such as epic poetry, drama, poetry and art, public oratory, legislative procedure, and Simplicius' philosophy. All papers present new approaches to their topics or ask new and provocative questions.